2019
DOI: 10.3390/ijms20133148
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular RNAs as Biomarkers of Sporadic Amyotrophic Lateral Sclerosis and Other Neurodegenerative Diseases

Abstract: Recent progress in the research for underlying mechanisms in neurodegenerative diseases, including Alzheimer disease (AD), Parkinson disease (PD), and amyotrophic lateral sclerosis (ALS) has led to the development of potentially effective treatment, and hence increased the need for useful biomarkers that may enable early diagnosis and therapeutic monitoring. The deposition of abnormal proteins is a pathological hallmark of neurodegenerative diseases, including β-amyloid in AD, α-synuclein in PD, and the transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 229 publications
(304 reference statements)
0
39
1
1
Order By: Relevance
“…After sufficient time had passed, the results were then gathered and analyzed, and the authors found that 545 participants had passed away from ALS. The results of this study did not suggest there was any significant association between caffeine and ALS pathology to be protective or adverse [121].…”
Section: Neurotrophic and Other Factors Involved In Alscontrasting
confidence: 85%
“…After sufficient time had passed, the results were then gathered and analyzed, and the authors found that 545 participants had passed away from ALS. The results of this study did not suggest there was any significant association between caffeine and ALS pathology to be protective or adverse [121].…”
Section: Neurotrophic and Other Factors Involved In Alscontrasting
confidence: 85%
“…Furthermore, recent works have depicted their role as next-generation biomarkers based on their feasibility as therapeutic drug-delivery nanocarriers. In immunotherapy, they have generated much excitement as candidates for diagnostics and therapeutics in an array of diseases [24][25][26][27][28]. In this current study, we performed ultrastructural characterization of BDEV, their biogenesis, and identification of signatures using quantitative mass spectrometry-based proteomics from male and female Sprague Dawley rats following either long-term nicotine or saline self-administration.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid diagnosis and intervention in the disease process could be beneficial in slowing neurodegenerative disease progression as well as facilitating the testing of new therapies. In ALS/MND, the average time from diagnosis to death is typically short (2–5 years) and it is not unusual for patients to wait a year before receiving a diagnosis [ 1 ]. Since disease progression correlates with motor neuron loss, early intervention could be critical for the development of new effective drug therapies.…”
Section: Introductionmentioning
confidence: 99%
“…To date, an ALS/MND diagnosis is based on clinical features with the elimination of alternative diagnoses and supporting data retrieved from electromyograms, nerve conduction studies, muscle biopsies, magnetic field imaging and biofluid analysis [ 3 , 4 ]. The search for ALS/MND biomarkers useful for diagnosis, prognosis and analysis of drug efficacy includes a variety of molecules found in biofluids and other techniques including: heavy and light chain neurofilaments, TAR DNA-binding protein 43 (TDP-43), a lipid peroxidation product (4-hydroxy-2,3-nonenal), a urinary neurotrophin receptor p75 extracellular domain, cystatin C, mRNA, miRNA, extracellular glutamate, markers of inflammation, microglial activation, electrical impedance myography, rate of disease progression, spinal cord imaging and others [ 1 , 5 17 ]. Thus far, none of these biomarkers have been sufficiently validated to be incorporated into the clinical standard of care [ 1 , 3 , 9 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%